Strengthening Pancasila Values in Adolescents in Malang Regency - Kasmin, Kasmin (Abdimas Indonesian Journal, 2024)
The phenomenon of globalization has implications for massive changes in people's lives. One manifestation of this influence is the accelerated digitalization of technology in all areas of life. This makes people need internet access to support their activities. The steps taken in carrying out this community service activity are by inviting partners to work together in holding several activities, including: 1) forming a marawis group for teenagers; 2) holding regular monthly religious studies that discuss the material on faith, morals and sharia; and 3) determining the schedule of activities. From the results of the activities as described above, it can be concluded that the activities that have been carried out include counseling. has had a positive impact on strengthening Pancasila values.